Jak badać literaturę dokumentu osobistego, czyli bliskie spotkania z Bronisławą Waligórską - Kwiatkowska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The author of 19th-century letters, Bronisława Waligórska – a socialist activist – was arrested and imprisoned in the Warsaw Citadel in July 1886. She sent letters from prison to her sister Jadwiga, who visited her in an attempt to satisfy the prisoner’s most pressing needs. The surviving correspondence is a testimony of the living conditions of the Citadel’s prisoners and the internal life of Bronisława, who was gradually losing her spirit and the will to fight. On December 31, 1886, she swallowed sulphur from matches and died a few days later. Waligórska’s letters are a testimony of the time spent in prison, but not only. In the letters to her sister, she discussed such topics as the conditions of everyday existence, life in prison and organisation, but also included her reflections on culture, literature and art. She tried to fill her time in prison with translation work. The surviving letters have been published in an innovative graphic form and their edition is a breakthrough in editorial work on archival documents. The print meticulously keeps all the corrections and crosses of the original. Monika Rudaś-Grodzka treated Bronisława Waligórska’s letters with great respect; she approached them with a passion and sensitivity of an archivist who not only analyses the content of the remaining documents, but is always aware that they are a testimony of the life of a particular person. Thanks to the peculiar attitude of the researcher, Waligórska, while being the protagonist of the book, never stopped being its author. The edition of letters from prison are accompanied by an editor’s note, a description of the terms of publications, a timeline, the main protagonist’s prison biography and a selection of documents concerning the investigation.